La resolución de problemas en el proceso enseñanza aprendizaje de la Matemática en décimo año E.G.B. De la U.E. " Manuel Gonzalo A. Rumazo". - Tapia Chacón, Sonia Elizabeth (2020)
Mathematics is a fundamental discipline of the Curriculum at all levels of Basic General Education, making its learning essential for the development of logical-critical thinking. In this context, the Tenth Year students of the "Manuel Gonzalo Albán Rumazo" Educational Unit of the Aláquez parish, present great shortcomings in solving mathematical problems, which generates the need to carry out this study, which has the general objective of developing a Base algorithm to improve problem solving in the teaching-learning process of mathematics in Tenth Year EGB students The research responds to a non-experimental methodological design with a qualitative and quantitative approach, for the collection of information techniques such as: the survey and observation were used. The results made it possible to structure a “Base algorithm for solving mathematical problems in Tenth Year students of E.G.B of the Manuel Gonzalo Albán Rumazo Educational Unit in the 2018-2019 school period”. This pedagogical tool was validated through the criteria of users, experts and socialization, reaching the following conclusion: The basic algorithm for solving mathematical problems is viable in its application due to its structure and feasibility, it proposes to be an effective solution to the problem.